2018
DOI: 10.1007/s00134-018-5273-y
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid functional status as a predictor of 1-year mortality and functional status in intensive care patients aged 80 years or older

Abstract: Of very old ICU patients, 62% were alive 1 year after ICU admission and 78% of the survivors had a functional status comparable to the premorbid situation. A poor PFS doubled the odds of death within a year. Knowledge of PFS improved the prediction of 1-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 38 publications
3
35
1
Order By: Relevance
“…Like other studies detailing the prediction of physical long-term health post ICU admission, we have shown that among our predictors the pre-ICU QoL is by far the most important predictor for long-term QoL (used as the sole predictor a-R 2 = 51.1%) (37)(38)(39). Conversations about pre-ICU health status are already an important part of many ICU physician's manner of providing care.…”
Section: Discussionsupporting
confidence: 59%
“…Like other studies detailing the prediction of physical long-term health post ICU admission, we have shown that among our predictors the pre-ICU QoL is by far the most important predictor for long-term QoL (used as the sole predictor a-R 2 = 51.1%) (37)(38)(39). Conversations about pre-ICU health status are already an important part of many ICU physician's manner of providing care.…”
Section: Discussionsupporting
confidence: 59%
“…As expected, the proportion of patients with at least moderate impairment of performance status in our study (60%) was much higher than that reported in studies of general critically ill patients [17]. However, the rates of performance status impairment found in our study are even higher than that found in some cohorts of elderly critically ill patients [22], suggesting that cancer burden may impact negatively on performance status of very old patients.…”
Section: Plos Onecontrasting
confidence: 56%
“…Additionally, because the ideal outcome for our patients is to return to their preexisting state or a state expected for a person of the same age and medical condition ( 4 ), insight in the pre-ICU health status may guide the treatment decision-making ( 14 , 18 ). Previous studies that did assess the pre-ICU health status focused often on one specific patient group, such as patients of 80 years old or older ( 26 ), or on one specific pre-ICU health domain, for example, cognitive functioning ( 13 , 27 ), frailty ( 21 ), or quality of life ( 28 , 29 ).…”
mentioning
confidence: 99%